Nonlinear and sex-specific associations of vitamin D metabolites with inflammatory blood markers in 125,537 adults - Li, Xitong; Chen, Xin; Liu, Yvonne; Wang, Jingyun; Hocher, Carl-Friedrich; Reichetzeder, Christoph; Elitok, Saban; Krämer, Bernhard; Schönbunn, Anne; Doebis, Cornelia; Huesker, Katrin; Baehr, Volker von; et al. (Nutrients, 2025)
Background: Vitamin D is increasingly recognized as a key immunomodulatory nutrient, influencing innate and adaptive immune responses. While 25-hydroxyvitamin D [25(OH)D] is widely used to assess vitamin D status, the active form, 1,25-dihydroxyvitamin D [1,25(OH)2D], may exert distinct effects on immune function. This study investigates the concentration-dependent and sex-specific relationships of both vitamin D metabolites with systemic inflammatory markers in a large clinical cohort. Objectives: To characterize the associations of 25(OH)D and 1,25(OH)2D with total white blood cell (WBC) count and leukocyte subtypes, including neutrophils, lymphocytes, monocytes, eosinophils, and basophils. Methods: We conducted a retrospective cross-sectional analysis of 125,537 adults (37.9% male; age 18–89 years) from routine laboratory diagnostics collected between 2014 and 2020 in Germany. Serum 25(OH)D and 1,25(OH)2D were measured using standardized chemiluminescent immunoassays. Inflammatory markers were assessed via automated hematology. Multivariable-adjusted linear and non-linear regression models were used to assess associations, adjusting for age, sex, and season. Results: Neutrophils and Monocytes: Displayed U-shaped associations with both 25(OH)D and 1,25(OH)2D. Neutrophil counts were lowest at 25(OH)D levels of ~40–60 nmol/L and increased significantly at both lower and higher extremes (p < 0.001). Lymphocytes: Inverse relationship with 25(OH)D (p < 0.001), and an inverse U-shaped relationship with 1,25(OH)2D, peaking at ~90 pmol/L, with counts decreasing at both lower and higher levels (p < 0.001). Sex-specific analysis revealed that the relationship between 1,25(OH)2D and lymphocyte count remained independent only in men, Eosinophils and Basophils: Demonstrated consistently negative correlations with both forms of vitamin D across all concentration ranges (p < 0.001). Conclusions: Our findings reveal distinct, concentration-dependent associations between vitamin D metabolites and leukocyte profiles, with evidence for nonlinear and sex-specific immunological effects. Both low and high levels of 25(OH)D and 1,25(OH)2D were linked to increased neutrophil and monocyte counts, suggesting that vitamin D excess, like deficiency, may be linked to low-grade inflammation. These data are hypothesis-generating and suggest that personalized monitoring of vitamin D status may be relevant for future research on immune health, particularly in populations at risk for inflammatory or metabolic disease, but they do not provide a basis for clinical decision-making.